Hubungan Tingkat Kemandirian Lansia dengan Perilaku Personal Hygiene - Hakim, Adinda Maulida; Hartati, Elis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the relationship between the level of independence of the elderly and personal hygiene behavior. This research method uses a correlational descriptive quantitative study approach using bivariate Spearman rank analysis. Data collection used the Katz Index questionnaire and personal hygiene questionnaire. The research showed that 90.2% of older people were wholly independent, and 63.9% of older people were good at personal hygiene. The results of the Spearman rank test show a relationship between the level of independence of the elderly and personal hygiene behavior with a value of p = 0.000. In conclusion, older people are in good condition. They can carry out all their activities independently and have good personal hygiene behavior. There is a relationship between the level of independence of the elderly and individual hygiene behavior. Keywords: Elderly, Personal Hygiene, Level of Independence